Effect of IVa group elements on the wettability between SiC and molten aluminum - CHOH, Takao; OKI, Takeo; HIBINO, Atsushi (Journal of Japan Institute of Light Metals, 1985)
The wettability of molten aluminum alloys containing 5% of Ti, Zr and Hf in IVa group to SiC was measured by the dipping method at 1273 to 1373K. These elements have an effect to improve the wettability of aluminum to SiC. EPMA analysis shows that these elements are concentrated and form carbides at the SiC-aluminum alloy interface. The wetting process were analysed by an equation derived in the previous work. Activation energies for wetting were obtained as 335 and 327kj/mol for Al-Ti and Al-Zr alloys respectively, which are identical to those for pure aluminum and Al-V alloy. Plotting the values of k0 and τ obtained by theoretical analysis against atomic number of alloying elements, a periodic nature is found.